2005
DOI: 10.1002/jmv.20405
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and partial sequence analysis of human T cell lymphotropic virus type I in China

Abstract: A total of 145,293 serum samples were collected from volunteer blood donors in 13 provinces of China and tested for anti-HTLV antibody using an ELISA licensed in China. Thirty were positive for anti-HTLV by ELISA and 19 of those 30 samples were confirmed positive using a supplemental immunoblot assay. Anti-HTLV-I was detected only in samples from Fujian province (a Southern province) where the positivity rate was approximately 0.05%. The region encoding gp46 from 5 of the 19 antibody positive samples was ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 12 publications
0
24
3
Order By: Relevance
“…1). In details, among the 38 positives, 34 live in Fujian province, and the positive rate was 0.08% which is 2.5-fold of average level and 0.03% higher than the study in 2005 (Wang et al, 2005). Two positives live in Guangdong, and two in Zhejiang province.…”
Section: Introductionmentioning
confidence: 47%
See 2 more Smart Citations
“…1). In details, among the 38 positives, 34 live in Fujian province, and the positive rate was 0.08% which is 2.5-fold of average level and 0.03% higher than the study in 2005 (Wang et al, 2005). Two positives live in Guangdong, and two in Zhejiang province.…”
Section: Introductionmentioning
confidence: 47%
“…The epidemiology of HTLV-I/II in industrialized countries has been intensively investigated, and mandatory screening of blood supplies for HTLV-I/II was implemented in mid-1980s in most developed and several developing countries, yet no expanding investigation has been executed in China so far (Zeng et al, 1984;Chen et al, 1989;Geng et al, 1998;Cao et al, 1998;Wang et al, 2005;Ma et al, 2013) and also been considered as a non-endemic region. However, Gessain et al reported that the current number of HTLV carriers in the highly populated China is very probably much higher (Gessain and Cassar, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, in Fujian province, a southern coastal area of China, all isolates subjected to sequencing were identified as being of the Transcontinental subgroup [Wang et al, 2005]. Again, among the indigenous peoples of Hokkaido and Sakhalin, Russia, all individuals were of the Transcontinental subgroup [Syrtsev et al, 2000;Yamashita et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Other areas of Asia have lower prevalence rates or have not been studied with large cohort studies. That is the case of China, where prevalence in blood donors is 1.3 cases per 10,000 [60] or Taiwan where only 5.8 cases per 10,000 blood donors are seropositive [61]. Another hot spot for HTLV-1 is Caribbean countries, such as Jamaica, where seroprevalence ranges from 1.7 to 17.4% depending on the risk group [62], and Haiti, approximately 4% [63].…”
Section: Htlv-1 In Endemic Countriesmentioning
confidence: 95%